A framework of rough cultural algorithms in optimizing mobile web caching performance - Sulaiman, Sarina; Shamsuddin, Siti Maryam; Abraham, Ajith; Sulaiman, Shahida (Penerbit UTM Press, 2007)

(untitled)
The stipulation of internet content rises dramatically in recent years. Servers have become extremely powerful and the bandwidth of end user connections and backbones grow constantly during the previous decade. Nonetheless, users frequently experience poor performance in accessing web sites or downloading files primarily when they use mobile devices due to their limited storage, processing, display, power and communication resources.. The common cause of poor performance is due to the direct access to the server (e.g. pitiable performance of server-side applications or during burst crowds) and network infrastructure (e.g. long geographical distances, network overloads, etc.). Hence, the goal of this study is to propose Rough Set (RS) as a knowledge representation for uncertainty in data of client behavior and mobile event specification with resource dependencies to reduce latency by prefetching selected resources to resolve the problems in handling dynamic web pages. Simultaneously, Cultural Algorithms (CA) will be exploited to optimize the performance of proxy caching in accumulating the knowledge between each generation. Consequently, The proposed caching scheme, Rough Cultural Algorithm (RCA) is developed to materialise the caching policies.